Insights Into the Properties, Biological Functions, and Regulation of USP21 - An, Tao; Lu, Yanting; Yan, Xu; Hou, Jingjing (Frontiers in Pharmacology, 2022)
Deubiquitylating enzymes (DUBs) antagonize the process of ubiquitination by removing ubiquitin from their protein substrates. The role of DUBs in controlling various physiological and pathological process has been extensively studied, and some members have been potential therapeutic targets in diseases ranging from tumor to neurodegeneration. Ubiquitin-specific protease 21 (USP21) is a member of the ubiquitin specific proteases, the largest subfamily of DUBs. Although USP21 was discovered late and early research progress was slow, numerous studies in the last decade are gradually revealing the importance of USP21 in a wide variety of biological processes. In particular, the pro-carcinogenesis effect of USP21 has been well elucidated in recent two years. In the present review, we provide a comprehensive overview of the current knowledge of USP21, including its propterties, biological functions, pathophysiological roles, and cellular regulation. Limited pharmacological interventions of USP21 are also introduced, highlighting the importance of developing novel and specific inhibitors targeting USP21.